Determinants of child Immunization under expanded programme on Immunization (EPI) in a rural setting of Bangladesh - Adhikary, Minati; Haque, Rumana; Tanira, Shaorin (Journal of Dhaka Medical College, 2015)
Objective: The aim of the study was to evaluate immunization status of children aged 12 to 23 months and to find out reasons for non-immunization and partial immunization, if any, under national Extended Programme on Immunization (EPI). Methods: This cross sectional study was done among a representative sample of 249 mothers/ principal caretakers of children under 2 years of age from households with varying socioeconomic status and with varying levels of education, from a rural setting, village Mulaid under Telihati union at Sreepur Upozilla under Gazipur district, in between March and June of 2011. Results: The study found that 221 (88.76%) of the children were fully immunized (FI) with BCG, PENTA3, OPV3 and measles; 27 children (10.84 %) were partially immunized and only 1 (0.40%) was non-immunized according to the recommendations used. Four of the children were missing full coverage of PENTA, seven of the children were missing OPV, 8 children were missing BCG where as 9 children were missing measles. The vaccination rate increased with an increase in the age of the children and the education level of the mother. Children of older mothers were more likely to have had the correct vaccinations. The mothers knowledge of and attitudes to vaccination showed a strong relationship with the vaccination status of their children. When the coverage rate for each vaccine was taken separately, the economic level of the households significantly affected the vaccine coverage. Most vaccinations occurred in public outlet agencies. Postponement of immunization due to the illness of the child, mothers lack of information about place, schedule and eligible age of immunization, parental lack of knowledge for the need for vaccines and family size constituted the main reasons for partial /onimmunization. A significant number of children in this study were found to be lacking recommended immunizations for age; a large number of their mothers stated that they did not know further vaccines were needed. Future efforts targeting immunization must emphasize better education of parents. Conclusion: It was concluded that lack of appropriate information is still the main hurdle for success of primary immunization in rural areas. Improvement could be achieved by improving IEC activities especially among females, as well as making this program success by putting all efforts in the case of EPI. DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21543 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 201-206